Reconstruction of full thickness abdominal wall defect following tumor resection: A case report - Kovačević Predrag; Veličkov Asen V.; Stojiljković Danilo; Veličkov Aleksandra I.; Ćeranić Zoran (Srpski Arhiv za Celokupno Lekarstvo, 2014)
Introduction. Reconstruction of a full thickness abdominal wall defect is a demanding procedure for general and also for plastic surgeons, requiring vigorous planning and reconstruction of three layers. Case Outline. We present a case of a 70-year-old patient with a huge abdominal wall tumor with 40 years evolution. Surgery was performed under general anesthesia. Full thickness abdominal defect appeared after the tumor resection. Reconstruction followed in the same act. The defect was reconstructed using a combination of techniques, including omental flap, fascia lata graft, local skin flaps and skin grafts. After surgery no major complications were noted, only a partial skin flap loss, which was repaired using partial thickness skin grafts. The final result was described by the patient as very good, without hernia formation. Conclusion. Omenthoplasty, abdominal wall reconstruction in combination with free fascia lata graft and skin grafts can be one of good options for the reconstruction of full thickness abdominal wall defects.